2015
DOI: 10.1186/s12876-015-0322-2
|View full text |Cite
|
Sign up to set email alerts
|

“And then you start to loose it because you think about Nutella”: The significance of food for people with inflammatory bowel disease - a qualitative study

Abstract: BackgroundMany patients with inflammatory bowel disease strongly believe that food or certain food products heavily influence the symptoms or even trigger acute flare-ups. Unfortunately, there is no generalizable information for these patients, and therefore no effective diet has been identified to date.MethodsThe narrative interviews we used for this study provide the basis for the German website www.krankheitserfahrungen.de. Maximum-variation sampling was used to include a broad range of experiences and a va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(62 citation statements)
references
References 29 publications
2
59
0
1
Order By: Relevance
“…The findings of this study lend support to previous research on the relationship between diet and IBD among adult patients. In particular, avoidance of and challenges to abstaining from trigger foods have been documented among adult patients with IBD (Fletcher & Schneider, 2006;Palant et al, 2015;Schneider et al, 2009). Fletcher and Schneider (2006) also briefly reported on healthy eating among their participants.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The findings of this study lend support to previous research on the relationship between diet and IBD among adult patients. In particular, avoidance of and challenges to abstaining from trigger foods have been documented among adult patients with IBD (Fletcher & Schneider, 2006;Palant et al, 2015;Schneider et al, 2009). Fletcher and Schneider (2006) also briefly reported on healthy eating among their participants.…”
Section: Discussionmentioning
confidence: 99%
“…Her mother (M5) indicated that the family had reduced rather than eliminated the consumption of pasta "because it was something that we were so accustomed to eating all the time." Difficulty in abstaining from trigger foods had also been reported among adults and young adults with IBD (Fletcher & Schneider, 2006;Palant et al, 2015;Schneider et al, 2009).…”
Section: Food Avoidance and Moderationmentioning
confidence: 93%
See 2 more Smart Citations
“…Uznali, że dylematy dotyczące wyboru produktów w takich sytuacjach są dla nich na tyle stresujące, że aby ich unikać, wybierają izolację społeczną. Istnieje zatem potrzeba holistycznej opieki dietetycznej złożonej zarówno z edukacji żywieniowej, jak i psychodietetycznej pracy z pacjentem [23].…”
Section: Leczenie Dietetyczne W Przypadku Nieswoistych Chorób Zapalnyunclassified